Weathering and mineralogical variation in gneissic rocks and their effect in Sangrumba Landslide, East Nepal - Regmi, Amar Deep; Yoshida, Kohki; Dhital, Megh Raj; Pradhan, Biswajeet (Springer Verlag, 2014)
Sangrumba landslide is one of the largest and the most active landslides in Nepal Himalaya. Geologically the landslide belongs to the Higher Himalaya and consists of Pre-Cambrian biotite–garnet and sillimanite gneiss with some quartzite. The present paper aims at describing various degrees of rock weathering and their effect in Sangrumba landslide. Field study followed by mineralogical, geochemical and geotechnical analyses of the collected rock and soil samples from the landslide zone were used in characterizing weathering degree. The gneisses are intensely weathered while quartzite is unweathered. Petrographical and X-ray diffraction analyses showed that the rocks in the landslide zone had undergone weathering process with the formation of different types of clay minerals as kaolinite, vermiculite, smectite and chlorite. This was further confirmed by the Scan Electron Microscope and Energy Dispersive X-ray analyses. These clay minerals drastically reduced the rock strength facilitating the extensive failure of the Sangrumba landslide. The major and trace element composition of the rock and soil samples was calculated from the XRF analyses. The geochemical analyses and weathering indexes of rocks showed that they are significantly weathered and had a major influence in the formation of the Sangrumba landslide. In addition, mechanical strength measurement of rock/soil showed that the strength drastically decreases as the weathering intensity increases. Rainfall followed by the rock type are the most dominant parameters influencing the weathering process which leads to the formation of large landslide as the present one. These findings can be used in other areas with similar geological and topographical conditions.